Attaining Automaticity in the Visual Numerosity Task is Not Automatic - Speelman, Craig P.; Muller Townsend, Katrina L. (Frontiers in Psychology, 2015)
This experiment is a replication of experiments reported by Lassaline and Logan (1993) using the visual numerosity task. The aim was to replicate the transition from controlled to automatic processing reported by Lassaline and Logan, and to examine the extent to which this result, reported with average group results, can be observed in the results of individuals within a group. The group results in this experiment did replicate those reported by Lassaline and Logan, however one half of the sample did not attain automaticity with the task, and one third did not exhibit a transition from controlled to automatic processing. These results raise questions about the pervasiveness of automaticity, and the interpretation of group means when examining cognitive processes.